K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 6 2018

2   \(x^7+x^5+1=x^7+x^6+x^5-x^6+1=x^5\left(x^2+x+1\right)-\left(x^6-1\right)=x^5\left(x^2+x+1\right)-\left(x^3-1\right)\left(x^3+1\right)\)

\(=x^5\left(x^2+x+1\right)-\left(x-1\right)\left(x^2+x+1\right)\left(x^3+1\right)=\left(x^2+x+1\right)\left(x^5-\left(x-1\right)\left(x^3+1\right)\right)\)

\(=\left(x^2+x+1\right)\left(x^5-x^4+x^3-x+1\right)\)

1   \(x^3-5x^2+3x+9=x^3+x^2-6x^2-6x+9x+9=x^2\left(x+1\right)-6x\left(x+1\right)+9\left(x+1\right)\)

\(=\left(x^2-6x+9\right)\left(x+1\right)=\left(x-3\right)^2\left(x+1\right)\)

26 tháng 6 2018

(​x+2)[(x+3)-(x+5)]=0

suy ra (x+2)(x-x+3-5)=0

-2(x+2)=0

suy ra x+2=0 suy ra x=2

26 tháng 6 2018

a ) ( x + 2 )[ ( x + 3 ) - ( x + 5 ) ] = 0 

      ( x + 2 )( x - 2 ) = 0 

      x^2 - 4 = 0 

      x^2 = 4

      => x = 2